Improving Mathematical Critical Thinking Ability Through Realistic Mathematics Learning In JHS Students - Sutarni, Sri; Gatiniggsih, Rustiwi (Jurnal Riset Pendidikan Matematika, 2022)
Critical thinking is a structured way of thinking in making decisions and solving problems. Because the critical thinking ability in junior high school students is low, realistic mathematics learning is considered to be able to improve students' critical thinking ability. The purpose of the research in this article is to describe the improvement of mathematical critical thinking ability through realistic mathematics learning reviewed from indicators and the averages increase each cycle. This type of research is Class Action Research that is carried out in 2 cycle. The research subjects consisted of mathematics teachers and 16 students of class VIII Muhammadiyah 5 Junior High School Surakarta. The data analysis technique in this study is qualitative descriptive to identify students and teachers during the mathematics learning process. The results of student work, data analysis are done by giving a score on each indicator. Score 1 if correct and score 0 if wrong. The results showed that the application of realistic mathematics learning improving the ability to think critically of mathematics. The average increase in mathematical critical thinking ability is 23.75% in pre-cycle, 71.25% in cycle I, and 85% in cycle II.